Determinants of fatigue in patients with Marfan syndrome: a study using PROMS - Ines Cavalier; Leslie Toko Kamga; Laurence Morin; Laurence Bal; Laurence Faivre; Guillaume Jondeau; Viet-Thi Tran; Olivier Milleron (Orphanet Journal of Rare Diseases)
Abstract Background Fatigue is often reported by individuals with Marfan syndrome (MFS). However, the determinants of fatigue and its impact on the daily lives of patients with MFS remain poorly understood. We sought to assess the level of fatigue and its determinants in individuals with MFS. Methods We conducted a cross-sectional study in ComPaRe Marfan, an e-cohort of MFS patients. Fatigue was assessed using the FACIT questionnaire already used in a wide range of chronic diseases. Pain and its interference with daily life were assessed using the Brief Pain Inventory. We performed univariate and multivariable linear regressions to identify determinants of fatigue. Results A total of 162 people with MFS completed the FACIT-Fatigue questionnaire. The median age was 46 and 59% were women. The median FACIT-Fatigue score was 31(IQR 22–39) and over ¾ of the cohort had a FACIT-Fatigue score below 40 corresponding to at least some level of fatigue. In the multivariate model, only pain interference was associated with fatigue (Coeff= -0.34, CI95%: [-0.46; -0.22], p < 0.001). Beta-blocker treatment, history of aortic, lens or scoliosis surgery were not associated with FACIT fatigue score. In addition, the FACIT fatigue scores was repeated every month during 3 months and were stable over time. Conclusion Fatigue is common in patients with MFS and is associated with pain that interferes with daily life. Therefore, pain management in MFS patients could improve quality of life and fatigue.